Feudal society in medieval France : documents from the County of Champagne - Evergates, Theodore (Middle Ages series., 1993)
Theodore Evergates has assembled, translated, and annotated some two hundred documents from the country of Champagne into a sourcebook that focuses on the political, economic, and legal workings of a feudal society, uncovering the details of private life and social history that are embedded in the official records.